The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1016/s1044-0305(03)00002-3
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and sensitive differentiation of anomers, linkage, and position isomers of disaccharides using High-Field Asymmetric Waveform Ion Mobility Spectrometry (FAIMS)

Abstract: A challenging aspect of structural elucidation of carbohydrates is gaining unambiguous information for anomers, linkage, and position isomers. Such isomers with identical mass can't be easily distinguished in mass spectrometry and a separation step is required prior to mass spectrometry identification. In our laboratory, gas-phase separation and differentiation of anomers, linkage, and position isomers of disaccharides was achieved using High-Field Asymmetric Waveform Ion Mobility Spectrometry (FAIMS). The FAI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
124
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(128 citation statements)
references
References 44 publications
2
124
0
Order By: Relevance
“…ϩ would be detected not only at its original transmission CV of 2.9 V but also at CVs where ions associated with their fragmentation product [MNH 4 ] ϩ are transmitted through FAIMS. Low-energy conditions at the mass spectrometer interface help to differentiate ions formed in ESI from their dissociation products" [22]. In our study, we also observed oligosaccharide aggregate ion formation and dissociation at the MS interface.…”
supporting
confidence: 60%
See 1 more Smart Citation
“…ϩ would be detected not only at its original transmission CV of 2.9 V but also at CVs where ions associated with their fragmentation product [MNH 4 ] ϩ are transmitted through FAIMS. Low-energy conditions at the mass spectrometer interface help to differentiate ions formed in ESI from their dissociation products" [22]. In our study, we also observed oligosaccharide aggregate ion formation and dissociation at the MS interface.…”
supporting
confidence: 60%
“…Gabryelski et al investigated the use of ESI-FAIMS-MS for oligosaccharide separation, and explored the addition of various salts to the sample solvent solutions for their effects on ionization and FAIMS selectivity [22]. ϩ would be detected not only at its original transmission CV of 2.9 V but also at CVs where ions associated with their fragmentation product [MNH 4 ] ϩ are transmitted through FAIMS.…”
mentioning
confidence: 99%
“…However, FAIMS was not widely used until its coupling to electrospray ionization mass spectrometry [8,9], which has expanded its utility to environmental [10 -13] and biological [14 -18] applications, in addition to traditional detection of airborne volatiles [19 -23]. The recent advent of commercial FAIMS systems (Ionalytics Selectra [17,24] and Sionex DMS [23,25]) is increasing the acceptance of FAIMS and diversifying its applications.While FAIMS analyses have become increasingly common, the fundamentals remain relatively poorly understood [18]. Phenomenologically, ions are separated by the difference between mobilities at high and low electric fields (E) (respectively K H and K L ) that in general differ as ion mobilities in gases depend on the field.…”
mentioning
confidence: 99%
“…While FAIMS analyses have become increasingly common, the fundamentals remain relatively poorly understood [18]. Phenomenologically, ions are separated by the difference between mobilities at high and low electric fields (E) (respectively K H and K L ) that in general differ as ion mobilities in gases depend on the field.…”
mentioning
confidence: 99%
“…26 Coupling of atmosphericpressure ionization techniques (ESI, APCI) via FAIMS to MS was explored starting in the late 1990's by Guevremont and colleagues, 27,28 who also showed that the cylindrical FAIMS has an ion focusing effect due to electrical field gradients. 29 ESI-FAIMS-MS has been employed advantageously in proteomics applications, 30 analysis of polysaccharides, 31,32 and drug discovery activities. 33 It should be noted that FAIMS separates ions on a timescale which is compatible with those of both liquid chromatography and tandem MS. 33,34 This paper describes the results of a pilot study designed to assess the utility of FAIMS in the analysis of triazines and associated metabolites.…”
Section: Introductionmentioning
confidence: 99%